An lntercultural Criticism of New Testament Translations (translation. a transdisciplinary journal, 2022)
The aim of rhis srudy is ro show s i m i larities and differences berween Greek and Swahili l i texts of the New Tesrament , especially ar the lexical, morphological,syntactic, and semantic levels. It uses an i nrercultural approach char compares Greek, Lartin , and Swahili texts, and argues that rhere is a great deal of similarity berwecn the Greek and the Swahili languages ar the grammat ical level, except for the Greek deponent form, which has no formal equivalent in Swahili . One of rhe most striking lexical findings concerns  the mismatch berween the Greek form of Jesus's name and i ts Larin or Swahili translations. Borh Latin and Swahili do not have formal articles, wh i le the G reek language uses them even before proper names. The original, authentic, and meaningful form of Jesus's name is the Hebrew or Aramaic.